A Study on the Effects of Lower Extremity Proprioceptive Neuromuscular Facilitation Patterns on Stair Ambulation in Stroke Patients (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: stroke; stair ambulation; proprioceptive neuromuscular facilitation patterns; stroke impact scale and timed up and down stairs test